HUBUNGAN SELF-EFFICACY IBU DENGAN KEJADIAN STUNTING PADA ANAK USIA 6-59 BULAN DI WILAYAH PUSKESMAS PLUMBON KABUPATEN INDRAMAYU (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Stunting remains a major health problem in Indonesia. Self-efficacy is a key factor in shaping maternal nutritional behavior, which impacts child development. This study aims to analyze the relationship between maternal self-efficacy and the incidence of stunting in children aged 6-59 months in the Plumbon Community Health Center (Puskesmas) work area. This study used an observational analytical case-control design. The sample consisted of mothers with children aged 6-59 months. The total sample size for the case and control groups was 48, resulting in a total sample size of 96. Child nutritional status was measured based on the height/age z-score using the anthrocalc application. A height/age z-score <-2.0 SD was interpreted as stunting, while a height/age z-score ≥-2 SD +2 SD was interpreted as the control group. The minimum, maximum, median, and mean z-scores in the stunting group were -3.10, -2.00, -2.10, and -2.27 SD, respectively, while in the control group they were -0.90, +3.40, -1.30, and -0.83 SD, respectively. Maternal self-efficacy was measured using the GSE-12 questionnaire. The research data were tested using the Chi-square test. A p-value ≤ 0.05 indicates a significant relationship.The analysis results showed no significant relationship between maternal self-efficacy and the incidence of stunting in children aged 6-59 months in the Plumbon Community Health Center (PHC) work area (p > 0.05). Maternal self-efficacy in the low, moderate, and high stunting groups was 8 (16.67%), 36 (75%), and 4 (8.33%), respectively. In the control group, it was 4 (8.3%), 39 (81.3%), and 5 (10.4%). The conclusion of this study is that there is no significant relationship between maternal self-efficacy and the incidence of stunting in children aged 6-59 months in the Plumbo Community Health Center work area.